Mitigation of Lightning Hazards at the More Sensitive Points in Wind Farms Using Ant-Colony Optimization Technique - Abd-Allah, M. A.; Said, A.; N. Ali, Mahmoud (Institute of Advanced Engineering and Science, 2016)
The lightning energy can be very harmfull to the wind turbine farm components. This paper attempts to evaluate the overvoltages at the sensitive points in wind farm, using ATP-EMTP package program. Four cases were performed; a) the transient voltage distribution in the insulating layer of the control line, b) the transient voltage on the control equipment, c) the coupling voltage between the tower and the control, and, d) the transient voltage distribution in the wind turbine WT Generator, Boast transformers and grid. These cases were performed under different lightning current conditions and at conventional design and proper design of grounding system. The results show that the Ground Potential Rise (GPR) is reduced with using the proper design of wind turbine ground system, but the induced voltage at the control system will not affected. This work determines the optimum location of wind turbine at the areas of maximum lightning incidence. Ant Colony Optimization (ACO) technique is implemented to find the optimum wind farm location. This work enhances the protection strategy of the wind farms against lightning stroke.